Influenced of electron density on plasmonic behavior of coupled AU nanostructures - Liow, Chi Hao (2015)
Surface plasmon resonance has attracted extensive interest because it allows us to manipulate light in nanoscale which is of paramount importance for optoelectronic switching devices, information processing, biological and chemical sensing, particularly in the field of dynamic controlled device, which can be realized by in-situ charging the material via applying electric potential. In this dissertation, we focus on investigating the plasmonic far field (extinction spectra) and near field (field enhancement) properties of coupled nanostructure in response to charging effect. A Drude-Lorentz model can describes the charging effect on a material. By employing the dielectric constants with different amount of free electron density, we theoretically investigating the charging effects (increase of excess of electrons) on both isolated (monomer) and coupled (dimer) Au nanostructure. The Au dimers are constructed from sphere and ellipsoid monomers building blocks. The increase of charging level induces plasmon peak blue shifting. We find that plasmon shifting depends on the geometries of the nanostructure. Larger the geometrical factors, larger the plasmon shifts. Subsequently, we characterize the sensitivity from the slope of the plasmon shifts. As expected, ellipsoid-ellipsoid dimer exhibits the largest geometrical factor (5.41) among all nanostructures in this study and yields the largest plasmon shifts, thus has the highest far field sensitivity (-2.87) to the charging effect. The results calculate from numerical solution is in agreement with those from analytical solutions. We also have study the near field response to the charging effect for these coupled nanostructures. The near field can be characterized based on the average electric field enhancement factor of nanostructures. When increasing the excess electrons to the Au nanostructures, the enhancement spectra are blue shifted, the results are consistent with their far field counterpart. To quantify the sensitivity of the near field response to the charging effect, we calculate the enhancement ratio of each nanostructure as a function of different charging levels. Surprisingly, we find that the ellipsoid-ellipsoid dimer yields the lowest enhancement ratio among all nanostructures despite its largest value of enhancement factor, and shows the lowest sensitivity with the value of 0.48. This phenomenon is because of the strong distorted charges separation in the ellipsoid-ellipsoid dimer, which can be explained by the effective dipole moment model. To mimic the real system, we conduct a study on the charging effect on sphere-on-substrate. Attributing to the presence of substrate in close proximity, the plasmon band of Au sphere is broaden, which retards the plasmon shifting, hence lower far field sensitivity toward charging effect. Despite the lower value of enhancement factor, we find the sphere-on-substrate shows a comparable value of sensitivity as that of ellipsoid monomer. Overall, this work provides a guide in designing nanostructure, particularly in the sensing application. In addition, with this knowledge, we can extrapolate to other geometries such as nanoprism, nanobar, and their coupled structures.